RvD1 Attenuated Susceptibility to Ischemic AKI in Diabetes by Downregulating Nuclear Factor-κ B Signal and Inhibiting Apoptosis - Li, Zheng; Liu, Zhiwen; Lu, Hengcheng; Dai, Wenni; Chen, Junxiang; He, Liyu (Frontiers in Physiology, 2021)
Background: Resolvin D1 (RvD1) is a potent lipid mediator able to promote inflammatory resolution in many diseases. However, RVD1 levels were found to be downregulated in diabetes. In this paper, we hypothesize that downregulated RVD1 is responsible for the susceptibility to ischemic acute kidney injury (AKI) in diabetes. Methods：The serum RVD1 of diabetes kidney disease (DKD) patients or non-diabetic renal disease (NDKD) were detected through an ELISA kit. Diabetic nephropathy (DN) was induced by streptozocin (STZ) injection intraperitoneally. Renal ischemia-reperfusion was used to induce AKI. Blood urea nitrogen (BUN) and serum creatinine were determined using commercial kits to indicate renal function. Renal apoptosis was examined by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Real-time polymerase chain reaction (PCR) was used to detect the marker of inflammatory response. Western blot was used to detect the expression of nuclear factor (NF)-κB-related proteins. Results：Serum RVD1 were decreased in DKD compared with NDKD, and decreased serum RVD1 were related to worse renal function. In animal experiments, serum RVD1 and renal ALX levels were downregulated. RVD1 treatment could ameliorate renal function and pathological injury after ischemic injury in STZ-induced diabetic mice. RVD1 treatment also could inhibit the inflammatory response. Di-tert-butyl dicarbonate (BOC-2) treatment could deteriorate renal function and pathological injury after ischemic injury in non-diabetic mice. RVD1 could inhibit the NF-κB activation and suppress inflammatory response mainly by inhibiting NF-κB signaling. Conclusions：RVD1 attenuated susceptibility to ischemic AKI in diabetes by downregulating NF-kB signaling and inhibiting apoptosis. Down-regulated serum RVD1 levels could be the crucial factor for the susceptibility to ischemic AKI in diabetes.